Corpus-Based Analysis of Lexical Patterns in Malaysian Secondary School Science and English for Science and Technology Textbooks - N.S. Menon, Sujatha Menon (2009)
The teaching of Science in English in Malaysia has become an issue yet both teachers and material writers are operating in the dark, as they are teaching Science in English, when it is not quite known what scientific English is actually needed in schools. The first step into looking at the type of language used in schools and required of students for the study of Science in English language and of English for Science and Technology (EST) is, to create a corpus of the language used in these subjects. As there is no existing corpus of the language used in the teaching and learning of Science subjects, nor for the English for Science and Technology subject, this study aims to develop two corpora: one for the Science subjects and one for the English for Science and Technology subject. These corpora will be based on the language used in both the upper secondary Science textbooks and the English for Science and Technology textbooks from two textbook zones in Malaysia. These corpora will create a reference point for scientific and English for Science and Technology lexical patterns used in existing prescribed textbooks and would also aid materials writers and curriculum builders in the process of re-designing teaching materials in future. This thesis analyses the similarities and differences between the lexico-grammatical patterns of scientific English and ‘everyday’ general English language and between scientific English and the language used in the English for Science and Technology textbooks. As this study intends to look at word relationships which involve collocations and multi-word clusters, the concordance software, WordSmith Tools version 4.0 is used for the purpose of text analysis in this study. Through analyses of wordlists, concordance lines and keywords, the lexico-grammatical patterns of both the corpora are identified. The findings indicated that the English for Science and Technology textbooks from both zones were quite dissimilar, not only in vocabulary loading and distribution but also in content focus. This work has also uncovered the inadequacy of the English for Science and Technology textbook to cope with the language needs of the upper secondary Science students as even though there were many patterns shared between the English for Science and Technology and Science textbooks, the language used in the English for Science and Technology textbooks lacked variety. The Science corpus had a greater variety of phrases, prepositions and phrasal verbs than those formed in the English for Science and Technology corpus. The study also found that even though some of the collocations in the Science corpus had predictable flexible combinations, many other collocations could not be easily predicted as they were arbitrarily blocked by usage, thus creating genre specific collocations. The study also found that many of the words when in collocation or compound form often acquire extended meanings which are content specific. General English language grammar rules could not be used to infer the meanings of compound nouns as many of the elements in a compound do not retain their literal meaning and in fact acquire extended meanings. The creation of the Science and English for Science and Technology corpora together with the work done in this thesis on the lexis and phraseology of Scientific English used in prescribed textbooks, should be used as a platform for materials writers to design and develop more relevant and accurate English for Science and Technology textbooks and materials.